High-precision bus voltage control based on NLESO and TSMC predicted load current and grid voltage differential feedforward - Xie, Di; Wang, Liangliang; Zhang, Zhi; Wang, Shoumo; Kang, Longyun; Yao, Jigang (Frontiers in Energy Research, 2023)
Power battery test equipment is widely used in the production and testing of new energy vehicles and energy storage containers. To address the problem of DC bus voltage fluctuations affecting the high accuracy of battery-side output voltage and current, a high accuracy bus voltage control strategy based on extended state observe (ESO) load current estimation and grid voltage differential feed-forward is adopted on the basis of the traditional double closed-loop controller for bidirectional AC/DC converters, which can achieve fast suppression of DC bus voltage fluctuations in power battery test equipment without adding additional hardware sampling circuitry and meet the high precision output requirements of the system DC bus when external disturbances and grid uncertainties are present. Simulation and experiment results show that the control strategy has a good suppression effect on the DC bus voltage fluctuation and can effectively improve the accuracy of the DC side output voltage and current.